2020
DOI: 10.3389/fphys.2020.00163
|View full text |Cite
|
Sign up to set email alerts
|

May the Force Not Be With You During Culture: Eliminating Mechano-Associated Feedback During Culture Preserves Cultured Atrial and Pacemaker Cell Functions

Abstract: Cultured cardiomyocytes have been shown to possess significant potential as a model for characterization of mechano-Ca 2+ , mechano-electric, and mechano-metabolic feedbacks in the heart. However, the majority of cultured cardiomyocytes exhibit impaired electrical, mechanical, biochemical, and metabolic functions. More specifically, the cells do not beat spontaneously (pacemaker cells) or beat at a rate far lower than their physiological counterparts and self-oscillate (atrial and ventricular cells) in culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…However, the data were not shown, which made difficult an appropriate comparison between studies. Conversely, recent studies have suggested that blebbistatin and its non-fluorescent derivative (S)-nitro blebbistatin (Kepiro et al, 2014) may be more effective at improving survival and preserving the morphology of cultured rabbit SAN cells and ventricular myocytes (Kirschner Peretz et al, 2020;Reddy et al, 2018;Segal et al, 2019). Consistent with this, by analyzing a population of SAN cells within the same field of view, the present study found that blebbistatin and (S)-nitro blebbistatin help maintain cell morphology in a significantly larger number of cultured cells compared with treatments with M1018 or BDM (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the data were not shown, which made difficult an appropriate comparison between studies. Conversely, recent studies have suggested that blebbistatin and its non-fluorescent derivative (S)-nitro blebbistatin (Kepiro et al, 2014) may be more effective at improving survival and preserving the morphology of cultured rabbit SAN cells and ventricular myocytes (Kirschner Peretz et al, 2020;Reddy et al, 2018;Segal et al, 2019). Consistent with this, by analyzing a population of SAN cells within the same field of view, the present study found that blebbistatin and (S)-nitro blebbistatin help maintain cell morphology in a significantly larger number of cultured cells compared with treatments with M1018 or BDM (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, under certain culturing conditions, SAN cells undergo a rapid remodeling that alters their electrical signals and morphology (Segal et al, 2019;Yang et al, 2012), which may impact the accurate assessment of the spatiotemporal dynamics of signaling networks. Thus, a method is necessary to culture SAN cells under conditions in which their functional properties and morphology are minimally impacted (Kirschner Peretz et al, 2020) while allowing for the expression of genetically encoded biosensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, rabbits were sedated with ketamine and xylazine (0.1 mL/kg each) and anesthetized with sodium pentobarbital (200 mg/mL) diluted with heparin, administered through an intravenous cannula. After quick removal, the hearts were placed in a custom-made, silicone-covered chamber, and the SAN and right atrial tissues were separated, as previously described [10], while bathed in 37 • C Tyrode's solution (125 mM NaCl, 5.6 mM KCl, 1.2 mM NaH 2 PO 4 , 24 mM NaHCO 3 , 5.6 mM glucose, 1 mM MgCl 2 and 1.8 mM CaCl 2 , bubbled with 95% O 2 and 5% CO 2 ). Once separated from the surrounding atrial tissue, SAN tissue was processed as previously described [11] in order to obtain single spontaneously beating SANCs.…”
Section: San Cell Isolation and Culturementioning
confidence: 99%